2012
DOI: 10.1007/s12010-012-9603-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Crude Oil from the BP Oil Spill in the Marsh Sediments of Southeast Louisiana, USA

Abstract: The significant challenges presented by the April 20, 2010 explosion, sinking, and subsequent oil spill of the Deepwater Horizon drilling platform in Canyon Block 252 about 52 miles southeast of Venice, LA, USA greatly impacted Louisiana's coastal ecosystem including the sea food industry, recreational fishing, and tourism. The short-term and long-term impact of this oil spill are significant, and the Deepwater Horizon spill is potentially both an economic and an ecological disaster. Microbes present in the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…Agreeing with the high share of (alkylated) naphthalenes in the Prestige oil, the studied CĂ­es Island sediments contained a high portion of naphthylmethylsuccinate synthase nmsA genes (Acosta-GonzĂĄlez, RossellĂł-MĂłra, & MarquĂ©s, 2013b), related to fumarate-dependent activation of 2-methylnaphthalene (see Section 5.6.2). Biodegradation of crude oil in marsh sediments along the coasts of Alabama, Mississippi and Louisiana (USA), which were affected by the Deepwater Horizon Oil Spill in 2010, occurs to a significant part under sulphate-reducing conditions (Boopathy, Shields, & Nunna, 2012;Kimes, Callaghan, Suflita, & Morris, 2014;Natter et al, 2012). Likewise, sediments located in proximity to the Deepwater Horizon blowout site were found to contain increased abundances of deltaproteobacteria (particularly related to D. autotrophicum HRM2), functional genes related to anaerobic degradation of aromatic compounds and benzylsuccinates indicative of active anaerobic alkylbenzene degradation (Kimes et al, 2013).…”
Section: Marine/estuarine Systemsmentioning
confidence: 99%
“…Agreeing with the high share of (alkylated) naphthalenes in the Prestige oil, the studied CĂ­es Island sediments contained a high portion of naphthylmethylsuccinate synthase nmsA genes (Acosta-GonzĂĄlez, RossellĂł-MĂłra, & MarquĂ©s, 2013b), related to fumarate-dependent activation of 2-methylnaphthalene (see Section 5.6.2). Biodegradation of crude oil in marsh sediments along the coasts of Alabama, Mississippi and Louisiana (USA), which were affected by the Deepwater Horizon Oil Spill in 2010, occurs to a significant part under sulphate-reducing conditions (Boopathy, Shields, & Nunna, 2012;Kimes, Callaghan, Suflita, & Morris, 2014;Natter et al, 2012). Likewise, sediments located in proximity to the Deepwater Horizon blowout site were found to contain increased abundances of deltaproteobacteria (particularly related to D. autotrophicum HRM2), functional genes related to anaerobic degradation of aromatic compounds and benzylsuccinates indicative of active anaerobic alkylbenzene degradation (Kimes et al, 2013).…”
Section: Marine/estuarine Systemsmentioning
confidence: 99%
“…However, although microorganisms are known to regulate marsh biogeochemical reactions (6,23,24), predicting whether and how marsh microbial communities would respond to the DWH oil spill was a challenge because diversity had been understudied (8,16,25,26), and almost nothing was known about community functional redundancy that could enhance response and resistance (20,21,(27)(28)(29)(30). Initially, some DWH spill researchers proposed a swift microbial response (16,17) because microbes have the capacity to degrade constituent carbon compounds in oil (31)(32)(33)(34)(35) and earlier nutrient enrichment, metal exposure, and oiling experiments provided evidence that marsh communities could withstand low levels of disturbance from an oil spill (25,36). Short-duration studies based on research conducted during one sampling time or from Ïœ6 to 9 months of sampling events in 2010 and 2011 confirmed that the relative abundances and species richness for bacterial communities exposed to weathered oil residues changed through time and recognized a greater diversity among known hydrocarbon-degrading bacteria as the amount of petroleum hydrocarbon concentrations increased (37)(38)(39)(40).…”
mentioning
confidence: 99%
“…These prevalent groups of sulfate-reducers are considered major hydrocarbon degraders (32). Sulfate reduction, in general, has been linked to high rates of MC252 oil degradation in marsh sediments (34,37,69,99).…”
mentioning
confidence: 99%
“…For example, the bbs gene (beta-oxidation of benzylsuccinic acid), derived from Azoarcus and Thauera species, involved in anaerobic degradation of toluene, was enriched in the cloud. Anaerobic petroleum-degrading bacteria were also associated with marsh sediments, of Southeast Louisiana, which had been contaminated with crude oil from the BP spill (Boopathy et al 2012).…”
Section: Petroleum Microbiology In Deep Aqueous Environmentsmentioning
confidence: 99%